Antioxidant activity of ethanolic extract Tetragonula testaceitarsis propolis combined with of Lepisanthes amoena leaves - Yogi Pratama; Paula Mariana Kustiawan (Program Studi Farmasi Universitas Mandala Waluya, 2023)
The illnesses brought on by free radicals are a common source of health issues. Pathogenic processes and tissue damage are both significantly influenced by free radicals. Natural ingredients from Indonesia has been carried out for generations by the community with various kinds of treatments according to existing tribes, for example, such as kelulut bee (Tetragonula testaceitarsis) propolis and kokang (Lepisanthes amoena) leaves. Stingless bee propolis has several bioactivities to prevent diseases. The research about T. testaceitarsis propolis still limited. The purpose of this research to find out whether the combination of T. testaceitarsis propolis and L. amoena leaves extracts has antioxidant activity. Ethanol extract T. testaceitarsis. propolis and ethanol extract L. amoena leaves was collected and then tested for antioxidant activity using the DPPH method. The results showed that all three concentrations had very strong antioxidant activity. T. testaceitarsis propolis extract (50%) combined with L. amoena leaves (50%) showed strong antioxidant activity (92%) in 25 ppm concetration. Then 75% T. testaceitarsis propolis extract and 25% L. amoena leaves extract had the highest antioxidant activity (95%) at a concentration of 50 ppm concentration. This strong antioxidant activity was prospected to be continued as a pharmaceutical product.